8.5k views
0 votes
What is the transformation of
g(x) = 4 - {x}^(3)

User Bastyon
by
5.1k points

1 Answer

7 votes

Given the transformed function:


g(x)=4-x^3

We want to describe the transformation with respect to the parent function:


f(x)=x^3

The "negative" in front of x^3 makes the graph reflect about x -axis.

Then, we have another transformation. There is a "+4" at the beginning.

This shifts the graph 4 units up.

Thus, the function f(x) is transformed to g(x) by:

• Shifting 4 units up

,

• being reflected about the x-axis

We can show the graph of both the functions.


\begin{gathered} f(x)=x^3 \\ g(x)=4-x^3 \end{gathered}

Parent function is the red one.

Transformed function, g(x), is the blue one.

What is the transformation of g(x) = 4 - {x}^(3)-example-1
User Heldt
by
6.0k points